KODE BUDAYA DALAM PUISI JAWA MODERN - Akhmad Nugroho (Humaniora, 2009)
The modern Javanese poem “Wengi ing Pinggir Bengawan” (TheNight in the River Side) is a poem with a background taken from the“wayang” story in the Javanesse culture. That poem is loaded with adialogue between the figures Kunthi, the mother, and Adipati Awangga,the son. This paper explores the meaning of the poem using the culturalcode analysis.